Chapter 17 Live Documentary Social Cinema and the Cinepoetics of Doubt - Nelson, Kim (Taylor & Francis, 2024)
Frank Ankersmit tells historians of their mission: "You can approximate objectivity only as long as you sincerely despair of approximating it." It follows that it is incumbent upon anyone who represents the past to enter that struggle. Whether by keyboard or camera, historians who do not probe and question their suppositions may seek to represent the past, but they do not make history. A prime question for historiophoty is to ask what this struggle looks and sounds like projected off the page. This chapter considers the cinepoetics of historical objectivity through a model of moving images that rewinds the clock to the emergence of film on screens and traces a new path for cinema through to a digital reimagining of what Tom Gunning calls the "cinema of attractions." It explores the documentary methods of narration and reenactment in Sam Green's Live Documentary practice and analyzes the methods by which filmmakers become cine-historians through articulating the historians' dilemma by audiovisual means in the creation of moving history of shared experience and public spectacle.